Synthesis of silver nanoparticle using Portulaca oleracea L. extracts - Shahbazi Nafeseh; Varshosaz Jaleh; Asghari Gholamreza (Nanomedicine Journal, 2013)
Objective(s): To evaluate the influences of aqueous extracts of plant parts (stem, leaves, and root) of Portulaca oleracea L. on bioformation of silver nanoparticles (AgNPs).   Materials and Methods: Synthesis of silver nanoparticles by different plant part extracts of Portulaca oleracea L. was carried out and formation of nanoparticles were confirmed and evaluated using UV-Visible spectroscopy and AFM. Results: The plant extracts exposed with silver nitrate showed gradual change in color of the extract from yellow to dark brown. Different silver nanoperticles were formed using extracts of different plant parts. Conclusion: It seems that the plant parts differ in their ability to act as a reducing and capping agent.